THE EFFECT OF HIGH PRESSURE PROCESSING ON MAJOR STRUCTURAL PROTEINS OF RAINBOW TROUT FISH FILLETS - Ana-Andreea CIOCA; Sorin Daniel DAN; Vlӑduța Mӑrioara LUPӐU; Liora Mihaela COLOBATIU; Marian MIHAIU (Studia Universitatis Babeș-Bolyai. Chemia, 2018)
Fresh rainbow trout fillets are very perishable food products. Therefore, they cannot be stored at refrigeration temperatures for a long period of time. High pressure processing (HPP) can improve the quality of the fillets through microbial load control. As a result of this, the shelf-life of the product is extended. However, some physicochemical changes can appear. The aim of this study was to assess the degree of protein denaturation in rainbow trout fillets treated with various levels of high pressure. The results showed that protein denaturation is definitely higher for the fillets treated with higher pressure levels, in the range of 400 MPa/3 min – 600 MPa/6 min and lower for the fillets treated with lower pressure levels, in the range of 100 MPa/3 min – 200 MPa/6 min. The use of lower pressure levels is beneficial to the structural quality preservation of the fillets, but less effective concerning the microbial inactivation. Maintaining a good structural and nutritional quality of the product is not very useful in this case, because it cannot be combined with other great advantages offered by the HPP tools, namely microbial control and spoilage decline. Therefore, further studies should focus on readjusting (e. g. minimizing) the holding time and other possible parameters, without lowering the high levels of pressure.